2001
DOI: 10.1017/s0048577201000051
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological characteristics of narcissism during active and passive coping

Abstract: This study provides the first psychophysiological analysis of narcissism by measuring autonomic responses during active and passive anticipatory coping in 40 undergraduate men who scored high or low on the Narcissistic Personality Inventory (NPI). Compared to the low NPI group, the high NPI group showed greater preejection period (PEP) shortening, cardiac deceleration, and skin conductance response (SCR) habituation during anticipation of an aversive stimulus (p < .02). As expected, SCR and PEP reactivity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Importantly, whereas there are few studies that have examined psychopathy and HRV, we have previously shown that persons scoring high on this interpersonal/affective dimension actually have higher resting HRV not lower (Hansen et al, 2007). Other researchers using phasic HR responses also suggest that persons scoring higher on this dimension have greater vagally mediated cardiac activity (Kelsey et al, 2001). Thus taken together, the use of mutilation pictures, the low resting HRV, and the lack of evidence of psychopathic traits in the present study suggest that the SR pattern evident in the low HRV group is not one of attenuated responses to the unpleasant pictures.…”
Section: Discussionmentioning
confidence: 50%
“…Importantly, whereas there are few studies that have examined psychopathy and HRV, we have previously shown that persons scoring high on this interpersonal/affective dimension actually have higher resting HRV not lower (Hansen et al, 2007). Other researchers using phasic HR responses also suggest that persons scoring higher on this dimension have greater vagally mediated cardiac activity (Kelsey et al, 2001). Thus taken together, the use of mutilation pictures, the low resting HRV, and the lack of evidence of psychopathic traits in the present study suggest that the SR pattern evident in the low HRV group is not one of attenuated responses to the unpleasant pictures.…”
Section: Discussionmentioning
confidence: 50%
“…The data captured the frequency of skin conductance responses (defined as the number of peaks with amplitudes that were !.05 micromohs during the stimulus), a measure that other experiments with the same criterion have linked to levels of arousal (e.g., Kelsey, Ornduff, McCann, & Reiff, 2001;Sigmon, Fink, Rohan, & Hotovy, 1996;Sokhadze, 2007).…”
Section: Independent Variablesmentioning
confidence: 99%
“…It is well known that the emotional wellbeing of people with intellectual disability depends to a great extent on acceptance by parents and their social milieu in general. [42][43][44] Taking into consideration the narcissistic wound, 45 a phenomenon suffered by parents who seek their own transcendence in their children or deposit their future expectations in their children, one can understand why parents have a hard time accepting their child's disability. This psychological issue must be dealt with through proper and early diagnosis of intellectual disability, since the lack of a diagnosis constitutes an obstacle for resolution of parents' psychological trauma which in turn frequently leads to recurrent emotional maltreatment or even physical abuse.…”
Section: Level III Continued Practical and Psychological Supportmentioning
confidence: 99%
“…These activities, in addition to promoting the socialization process without the immediate risk of suffering social rejection, provide the possibility of eliminating the egocentricity of people with intellectual disability. 58 Activities are aimed at clients' learning to enjoy the company of others, share belongings, and choose appropriate recreational activities from what the community has to offer while supervising that behavior complies with social norms and rules.…”
Section: Level Ii-putting Independent Living Skills Into Practicementioning
confidence: 99%